A Provisional List of Unprovenanced, Twenty-First Century, Dead Sea Scrolls-like Fragments - Tigchelaar, Eibert J. C. 1959- (2017)
This article briefly discusses the Dead Sea Scrolls-like fragments that have surfaced in the twenty-first century and presents a full list of these fragments as known to the author.
Keywords: Dead Sea Scrolls -- provenance -- collections -- forgery